2021
DOI: 10.1080/1331677x.2020.1860794
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of tax avoidance – evidence on profit tax-paying companies in Romania

Abstract: Our objective is to investigate the determinants of tax avoidance in Romanian companies in 2013-2017. Our initial sample comprises 236 privately owned companies that are payers of profit tax and have been found guilty of tax evasion. This was matched with 236 'compliant' companies structured similarly by industry, whereas the final sample comprises 1674-year-observations. We defined 'compliant' those companies that have never been prosecuted for tax evasion. Our main finding is that larger companies with lower… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 66 publications
2
12
0
3
Order By: Relevance
“…Results of our research shows that Polish entrepreneurs are not using institutions to seek rent but they have to abide or obey them to survive. Our results confirm the observations formulated by Sauka and Welter (2007) on the nature of unproductivity in Central and Eastern European countries, at the same time, they can be used to indirectly support evidence from Romanian research (Mocanu et al, 2021). Entrepreneurs that were directly questioned about S.N.s regarding tax evasion and bribery, perceive tax fraud as acceptable but at the same time do not accept bribes.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Results of our research shows that Polish entrepreneurs are not using institutions to seek rent but they have to abide or obey them to survive. Our results confirm the observations formulated by Sauka and Welter (2007) on the nature of unproductivity in Central and Eastern European countries, at the same time, they can be used to indirectly support evidence from Romanian research (Mocanu et al, 2021). Entrepreneurs that were directly questioned about S.N.s regarding tax evasion and bribery, perceive tax fraud as acceptable but at the same time do not accept bribes.…”
Section: Discussionsupporting
confidence: 90%
“…However it needs time and knowledge, maybe that is why it is not so popular. The research conducted for the period 2013-2017 on tax avoidance in Romania indirectly shows that companies not at risk of bankruptcy are less prone to tax avoidance (Mocanu et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Kassa (2021) asserted that one of the leading drivers of tax evasion is economic factors. A study by Kong and Wang (201) corroborates this point, particularly, the researchers pinpoint income level, sources of income available to taxpayers, inspection rate, the financial penalty imposed for tax evasion, and the marginal tax rate as the main propagators of tax evasion (Mocanu et al, 2020). Middle-class people are more willing to comply with tax laws than lower and higher-income earners because they are more afraid of the financial and psychological consequences that they will suffer as punishment for tax evasion (Fuest and Riedel, 2009).…”
Section: Tax Evasion and The Causation Of The Phenomenonmentioning
confidence: 86%
“…In these results one can clearly observe the fear of getting into debt. Mocanu et al (2021) found that larger companies with lower financial performance and a lower leverage ratio are more inclined towards tax avoidance. The geographical region and the industry sector in which companies operate in, are also determining their tax avoidant-behavior.…”
Section: Discussionmentioning
confidence: 99%